1977
DOI: 10.1139/v77-405
|View full text |Cite
|
Sign up to set email alerts
|

N-Nitromethylphthalimide. A formyl anion equivalent

Abstract: It is shown that the exclusive 1,4-addition of N-nitromethylphthalimide 4a to unhindered α,β-unsaturated ketones and esters can be effected by non-nucleophilic bases, such as sodium hydride or potassium fluoride, in dimethyl sulfoxide. The phthalimido moiety can be removed from the adducts with hydroxylamine or 1,2-dianilinoethane to give the oximes or diphenylimidazolidines of 1,4-ketoaldehydes. The ethylene ketal 5 of 3-formylcyclohexanone could easily be recovered from the imidazolidine 10, but it was not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In this context, we have found that N-nitromethylphthalimide, which can be easily prepared from commercially available starting materials in a very simple way, [11] constitutes an excellent hydroxymetanimidoyl anion equivalent to be used as a Michael donor in enantioselective conjugate addition reactions with a,b-unsaturated aldehydes under iminium activation (see Scheme 1). [12] On one hand, N-nitromethylphthalimide is an acidic compound, which can participate as pronucleophile under the neutral or slightly basic reaction conditions associated to iminium catalysis, [13] therefore allowing the use of a chiral secondary amine catalyst to achieve enantiocontrol.…”
Section: In Memory Of Our Colleague and Friend Rafael Suaumentioning
confidence: 99%
“…In this context, we have found that N-nitromethylphthalimide, which can be easily prepared from commercially available starting materials in a very simple way, [11] constitutes an excellent hydroxymetanimidoyl anion equivalent to be used as a Michael donor in enantioselective conjugate addition reactions with a,b-unsaturated aldehydes under iminium activation (see Scheme 1). [12] On one hand, N-nitromethylphthalimide is an acidic compound, which can participate as pronucleophile under the neutral or slightly basic reaction conditions associated to iminium catalysis, [13] therefore allowing the use of a chiral secondary amine catalyst to achieve enantiocontrol.…”
Section: In Memory Of Our Colleague and Friend Rafael Suaumentioning
confidence: 99%
“…In our initial synthesis of target compounds 1 − 3 , the lipophilic side chain was introduced on the cyclohexane ring via the coupling of the mixed homocuprates,11a 18 and 23 , with 2-cyclohexen-1-one (Scheme ). A subsequent route involved the use of the Wadsworth−Horner−Emmons reaction between the ylide of a β-ketophosphonate 11b-d ( 26 or 27 ) and cyclohexanecarboxaldehyde 29 (Scheme ).…”
Section: Chemistrymentioning
confidence: 99%
“…Further reduction 15a of the methyl ester using DIBAL-H in toluene at −78 °C afforded the protected 3-oxocyclohexane carboxyaldehyde 29 . This aldehyde could be isolated and characterized but not stored more than several hours 11e. For this reason the reduction of the ester 28 had to be performed concomitantly to the formation of the ylide of the appropriate β-ketophosphonate ( 26 or 27 ) using sodium hydride in THF at −40 °C.…”
Section: Chemistrymentioning
confidence: 99%
“…IR: 2240,1702. 5-(2-Cyano-I-cyclooclen-1-yloxy)pentanoate (1 1) and Ethyl 5-(I-Cyano-2-oxocyclooc-fyLy[)pentanoate (12). A mixture of 1 (4.53 g, 30 mmol), ethyl 5-bromopentanoate (13; 12.54 g, 60 mmol), Bu,NOH (15.5 g, 60 mmol, 40% aq.…”
Section: Rearrangementmentioning
confidence: 99%
“…layer washed with H,O until neutral and dried. Workup and chromatography as described in Method A gave 4 (870 mg, 59.4%), cJ [12].…”
Section: Derivatives Of 2-oxocyclododecane-1-carbonitrile (2) 21 Mmentioning
confidence: 99%